2017
DOI: 10.1186/s12879-017-2660-x
|View full text |Cite
|
Sign up to set email alerts
|

Strategies for the prevention of perinatal hepatitis B transmission in a marginalized population on the Thailand-Myanmar border: a cost-effectiveness analysis

Abstract: BackgroundData on the cost effectiveness of hepatitis B virus (HBV) screening and vaccination strategies for prevention of vertical transmission of HBV in resource limited settings is sparse.MethodsA decision tree model of HBV prevention strategies utilised data from a cohort of 7071 pregnant women on the Thailand-Myanmar border using a provider perspective. All options included universal HBV vaccination for newborns in three strategies: (1) universal vaccination alone; (2) universal vaccination with screening… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 57 publications
0
12
0
Order By: Relevance
“…46 Similarly, universal HBV vaccination with birth dose was the least costly HBV prevention option in a population in Thailand with maternal seroprevalence of 7%. 116 Provision of HBIG for infants born to HBV infected women in Thailand was cost-effective at a willingness-to-pay threshold of $1200.…”
Section: Resultsmentioning
confidence: 99%
“…46 Similarly, universal HBV vaccination with birth dose was the least costly HBV prevention option in a population in Thailand with maternal seroprevalence of 7%. 116 Provision of HBIG for infants born to HBV infected women in Thailand was cost-effective at a willingness-to-pay threshold of $1200.…”
Section: Resultsmentioning
confidence: 99%
“…During the data collection, many sources of information were investigated regarding the HBV immunization status of a participant. A study conducted at the Thai-Myanmar border reported that administering HBV vaccines to people living in the border area was highly effective in preventing the disease [31].…”
Section: Discussionmentioning
confidence: 99%
“…According to the WHO, screening interventions are expected to provide treatment alternatives for those patients with identified cases of disease [ 1 ]. However, 15 studies (22%) failed to model a treatment pathway [ 22 24 , 26 , 29 , 31 , 38 , 44 , 57 , 64 , 70 74 ]. The main outcomes captured by these studies were the following: cases detected, missed cases, avoided cases, and identified true positives and true negatives.…”
Section: Resultsmentioning
confidence: 99%